Building Ohmic Contact Interfaces toward Ultrastable Zn Metal Anodes. Issue 23 (20th October 2021) - Liu, Huanyan; Wang, Jian‐Gan; Hua, Wei; Sun, Huanhuan; Huyan, Yu; Tian, Shan; Hou, Zhidong; Yang, Junchang; Wei, Chunguang; Kang, Feiyu
Abstract: Zn metal holds grand promise as the anodes of aqueous batteries for grid‐scale energy storage. However, the rampant zinc dendrite growth and severe surface side reactions significantly impede the commercial implementation. Herein, a universal Zn‐metal oxide Ohmic contact interface model is demonstrated for effectively improving Zn plating/stripping reversibility. The high work function difference between Zn and metal oxides enables the building of an interfacial anti‐blocking layer for dendrite‐free Zn deposition. Moreover, the metal oxide layer can function as a physical barrier to suppress the pernicious side reactions. Consequently, the proof‐of‐concept CeO2 ‐modified Zn anode delivers ultrastable durability of over 1300 h at 0.5–5 mA cm −2 and improved Coulombic efficiency, the feasibility of which is also evidenced in MoS2 //Zn full cells. This study enriches the fundamental comprehension of Ohmic contact interfaces on the Zn deposition, which may shed light on the development of other metal battery anodes. Abstract : A universal Zn‐metal oxide Ohmic contact interface model is demonstrated to effectively enable improved Zn 2+ diffusion kinetics and a reduced Zn nucleation barrier, thus achieving a dendrite‐free and side‐reaction‐free Zn deposition chemistry for significant improvement of the electrochemical performance in both the symmetric cells and full cells.